Video-Based Cultural Literacy to Support Intercultural Competence in Japanese Language Classes - Sri Wahyu Widiati (Universitas Negeri Semarang, 2023)
Intercultural competence needs to be possessed by students to become part of a global society. In line with that, the need for Japanese language learning that integrates between cultures is getting bigger. Original videos can be one of the sources of cultural literacy to expand intercultural experience and understanding. The objectives of this study are to (1) describe video-based cultural literacy activities by implementing intercultural pedagogic principles and (2) describe students' intercultural competencies, including the components of values, attitudes, and knowledge. The learning procedure is managed by intercultural pedagogic practices, which consist of (1) interaction, (2) paying attention, (3) comparing, (4) reflection, and (5) tentative conclusions. The research methodology used is descriptive qualitative. This study shows that the use of video in Japanese intercultural learning is beneficial as a source of information. Furthermore, implementing pedagogic practices is also helpful in providing clear guidelines for teaching and learning activities. Students' perceptions, as outlined in written sentences, can be known and analyzed based on the components of intercultural competence. Students can expand intercultural knowledge and improve intercultural understanding and competence through the use of video-based cultural literacy by implementing intercultural pedagogic practices Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalIntercultural CompetenceJapanese LiteratureJapanese Language Education